How does the web game design influence the behavior of e-banking users? - Rodrigues, L. F.; Costa, C.; Oliveira, A. (Computers in Human Behavior, 2017)
Gamification has a clear influence on software design, development and plays an important role in the motivation and intention of users to use a website and buy online. Nevertheless, in the case of e-banking, the influence of gamification in software design and on the user's intention to use are still very unclear. We intend to verify how game design elements and mechanics combined in the design of a bank website, influence the intention of customers to use e-banking. To explore and analyze the effects of gamification on a bank website, we propose a conceptual model considering the interaction between six variables: gamification, ease of use, information, design, web page characteristics, and intention to use the website. To test this model we develop a quantitative study involving 219 bank customers as participants who interacted with a gamified e-banking website to manage their financial investments. Participants then responded to an online questionnaire (including items related to the main variables), in order to measure their reactions to gamified software and their intentions. All data were statistically analyzed and results indicate that gamification has a significant influence on the ease of use and the intention to use ebanking, as well as on the web design, information, and webpage characteristics. We find that gamification may motivate customers to use e-banking, and that it improves their financial literacy and facilitates online processes and transactions. This study provides insightful guidelines for web design, development and e-banking contents that can be taken into account by marketing, IT, and business teams working in electronic banks.